Establishment of two species groups of Ichthyurus Westwood (Coleoptera: Cantharidae), with description of two new species from China and Vietnam - Lin, Han-Qing; Liu, Hao-Yu; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2024)
Two species groups of the genus Ichthyurus Westwood, 1848 in the Oriental Region are proposed based on the anatomical comparison. One is the I. vandepolli species group, which is composed of two species, namely I. vandepolli Gestro, 1892 and I. opacus Gestro, 1906 (newly recorded to China). The other is the I. bourgeoisi species group, consisting of four species, including I. bourgeoisi Gestro, 1892, I. savioi Pic, 1928, I. niger sp. nov. (Vietnam, Vinh Phue) and I. bilineatimimus sp. nov. (China, Yunnan). The above species are illustrated with habitus and genital segments of both sexes, prothoracic leg and aedeagus of the male and internal genitalia of the female. A key for identification and distribution maps of these species are provided.